2010
DOI: 10.1063/1.3521532
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of supercritical trapped internal waves over topography

Abstract: We consider the steady flow of a stratified fluid over topography in a fluid of finite vertical extent, as typified by experimental flumes with a rigid lid or the ocean under the rigid lid approximation. We do not specify a functional form of the upstream stratification or background current and derive a general version of the Dubreil–Jacotin–Long equation appropriate for the problem. This elliptic equation is strongly nonlinear and we develop an efficient, pseudospectral, iterative method for its numerical so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(36 citation statements)
references
References 22 publications
4
32
0
Order By: Relevance
“…Soontiens et al 25 also noted that in ISWs with trapped cores the density field was typically more stable than the velocity field. They presented a model for trapped core waves in the presence of a background shear flow.…”
Section: B Unsteady Behaviormentioning
confidence: 95%
See 2 more Smart Citations
“…Soontiens et al 25 also noted that in ISWs with trapped cores the density field was typically more stable than the velocity field. They presented a model for trapped core waves in the presence of a background shear flow.…”
Section: B Unsteady Behaviormentioning
confidence: 95%
“…Without exception, all steady state models of ISWs with trapped cores in the literature, that are evolved through time-dependent simulations result in weakly unstable or unstable waves. 18,19,[23][24][25] In the laboratory, both Grue et al 13 and Carr et al 14 have observed unstable ISWs with trapped cores. Grue et al 13 observed trapped cores in which small vortices took place in the leading part of the wave.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soontiens et al . studied trapped internal waves over isolated topography in the presence of a background shear.…”
Section: Introductionmentioning
confidence: 99%
“…This condition is satisfied when U 0 > c j , where c j is the conjugate flow speed. 27,28 One subcritical case for which upstream propagating modes are permitted is also considered. In this case, the background flow satisfies c l w < U 0 < c j , where c l w is the linear long wave speed.…”
Section: Methodsmentioning
confidence: 99%